2002
DOI: 10.1079/bjn2002733
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different cooking methods on folate retention in various foods that are amongst the major contributors to folate intake in the UK diet

Abstract: Folate intake is strongly influenced by various methods of cooking that can degrade the natural forms of the vitamin in foods. The aim of the present study was to determine the effect of different cooking methods on folate retention in various foods that contribute to folate intake in the UK diet. Typical purchasing and cooking practices of representative food folate sources were determined from a questionnaire survey of local shoppers (n 100). Total folate was determined by microbiological assay (Lactobacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
114
5
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(134 citation statements)
references
References 28 publications
11
114
5
4
Order By: Relevance
“…A correlation between the folate losses caused by various ways of cooking and the kind of vegetable (peas, broccoli, and potatoes) was recently mentioned by Stea et al (2006). Similar data were published by McKillop et al (2002) for spinach, though a lower retention value was found in broccoli. The results of the present experiments with cauliflower are close to the data published by Melse-Boonstra et al (2002) on the losses found after 8 min blanching.…”
Section: Retention Of 5-mthf During the Boiling Of Selected Vegetablessupporting
confidence: 66%
See 1 more Smart Citation
“…A correlation between the folate losses caused by various ways of cooking and the kind of vegetable (peas, broccoli, and potatoes) was recently mentioned by Stea et al (2006). Similar data were published by McKillop et al (2002) for spinach, though a lower retention value was found in broccoli. The results of the present experiments with cauliflower are close to the data published by Melse-Boonstra et al (2002) on the losses found after 8 min blanching.…”
Section: Retention Of 5-mthf During the Boiling Of Selected Vegetablessupporting
confidence: 66%
“…Leaching and oxidative degradation represent the main causes of the decrease of folate values in this case and may thus influence the folate intake. Extensive folate losses in the course of spinach and broccoli boiling were found by McKillop et al (2002). Steaming, in contrast, resulted in a minimal decrease of the folate content.…”
mentioning
confidence: 94%
“…Differences of folate forms from our study compared to other research may be attributed to discarding the soaking and cooking water rather than the destruction of folate forms during cooking [24,36]. However, legumes soaked overnight for 16 h have been shown to have higher folate retentions compared to no presoak or quick soak treatments [24].…”
Section: Folate Contentscontrasting
confidence: 68%
“…Folate content of the cooking water was not determined in our study. It has been suggested to use the cooking water from legumes for further consumption [36]. In Tajikistan, the most common way of preparing legumes is cooking the legume and using the water as broth for stew, soup or other food items.…”
Section: Folate Contentsmentioning
confidence: 99%
“…It should be noted that serum folate concentrations and dietary folate intake were only modestly correlated with each other (Spearman's rank correlation coefficient; 0.21 for men and 0.13 for women). This may be partly accounted for by reporting bias in dietary survey but other factors including cooking method (McKillop et al, 2002) and genetic factor (Bottiglieri, 2005;Gilbody et al, 2007a) should also influence. Specifically, methylenetetrahydrofolate reductase (MTHFR) is involved in folate metabolism (Bottiglieri, 2005;Gilbody et al, 2007a), Serum folate, homocysteine and depression A Nanri et al and those carrying MTHFR 677TT genotype have a lower serum folate compared with those carrying 677CC genotype independent of folate intake (Nishio et al, 2008).…”
Section: Discussionmentioning
confidence: 99%